Výsledky léčby u vybraných infertilních pacientek s vysokou denzitou endometriálních NK buněk CD56+ a CD16+ Druhá část - Ulčová-Gallová, Z; Pešek, M; Haschová, M; Chaloupka, P; Mukenšnabl, P; Cibulka, J; Lošan, P; Bibková, K; Mičanová, Z (Ceska gynekologie, 2018)
INTRODUCTION: This statements follows the first part of our publication entitled Screening of endometrial NK cells in selected infertile patients (First part - Methods and current results), where we dealt with methodology and endometrial findings of the natural killer cells CD16+ and CD56+. These cells are among the most important in preimplantaion, and in implantation period, in early pregnancy too, but can also negatively influence above mentioned processes. OBJECTIVE: We focused on the immunomodulatory treatment with intramuscular immunoglobulins in 21 infertile patients with a high density of endometrial NK cells CD16+ and CD56+. DESIGN: Original work-prospective study. SETTING: Genetics-Pilsen. METHODS: From the originally investigated 57 women aged 25-41 (average 34) years with their history of 3-9 abortions, we target on a high selective subgroup of 21 infertile patients with pathological density of endometrial NK cells CD56+ and CD16+. RESULTS: Twelve patients underwent immunomodulatory treatment with intramuscular immunoglobulin in time of positive HCG and went on the therapeutic scheme, nine infertile women continued with IVF-ET but did not achieve HCG positivity despite of initial treatment with immunoglobulins. Of the 12 treated patients, seven of them gave a birth to healthy babies, as to the next five pregnancies - one was extrauterine pregnancy, one genetically defective fetus, three pregnancies go on successfully.Nine women from the IVF program did not get pregnat. CONCLUSION: Immunomodulatory treatment with immunoglobulins also influences endometrial NK cells CD56+ and CD16+ associating with an overproduction of embryocytoxic cytokines. Treatment of our patients with the pathological endometrial density of NK cells must be solved strictly individually.
Keywords: CD56 Antigen; Killer Cells, Natural; natural killer cells endometrium.; Chorionic Gonadotropin; těhotenství; ženská infertilita; imunomodulace; Adult; immunoglobulins; Receptors, IgG; Endometrium; receptory IgG; Immunomodulation; Fertilization in Vitro; antigen CD56; choriogonadotropin; Infertility, Female; ženské pohlaví; Humans; Pregnancy; endometrium; treatment; fertilizace in vitro; dospělí; buňky NK; Female; infertility; lidé